Heat Tolerance in Donkeys and Mules - Pal, Yash; Gupta, Ashok K; Yadav, M P (Annals of Arid Zone, 2016)
Heat tolerance in adult indigenous donkeys, exotic donkeys (Poitu) and mules was studied for exposure to direct sun during hot dry period. There were no inherent differences in the rectal temperature and respiratory frequency under shade in the three breeds. Eight hours of exposure daily for six consecutive days caused a significant (P<O.05) increase in the rectal temperature in exotic and indigenous donkeys, while respiratory frequency increased significantly (P<O.OI) only in exotic donkeys. Further, in all the three groups, RR and RT values observed in the morning during and before the heat exposure period were very much similar. It suggests that all the equids in three groups were equipped with good thermolytic efficiency. Compared to the local donkeys and mules, the exotic donkeys were least heat-tolerant on exposure to direct sun, as judged from the higher increase in RT and RR, related possibly to the black/dark brown color of their hair that absorbs more incidental solar radiation.